Repair technique for wooden fishing boats using fibreglass. (November 2019) - Sunardi,; Sukandar,; Sulkhani Y, E; Rahman, M A
Abstract: Almost all fishing boats operating in Indonesia are made of wood. The hulls of wooden boats are exposed to heat everyday and float in seawater, a combination which can cause parts of the boat's hull to be quickly damaged. One type of damage that occurs all the time is the attachment of fouling organisms (animals and marine plants) which encrust the hull of the boat; therefore, the hull should be careened once a week, as otherwise resistance will increase, reducing the speed and increasing fuel consumption. Fibreglass is a composite material which is strong, weather resistant and easily formed. This composite material can be applied as a coating material for wooden boats to overcome weathering and repair leaks. This applied research directly practiced a method to repair wooden boats by coating with 2 layers of fibreglass. The stages included the removal of all fouling and other coatings (e.g. paint) and contamination, drying and repairs, coating with two layers of fibreglass, followed by finishing. The results showed that the use of fibreglass to repair wooden boats can be a very effective technique with the following advantages: boards of boat hulls that are immersed in water do not decay, so that there is less likelihood of leaks developing; the technique reduces outlay because maintenance costs of fishing boats are reduced; boat maintenance will be easier because it is only necessary to clean the fouling attached to the hull; longer boat life and greater hull strength, as protection with fibreglass can strengthen old wooden construction elements and enable them to last longer.